Waste to wealth: near-infrared/pH dual-responsive copper-humic acid hydrogel films for bacteria-infected cutaneous wound healing - Zha, Kangkang (2023)
The clinical applications of currently used photosensitizers are limited by high costs, inconvenient preparation, suboptimal biodegradability, and a lack of biological activity. Humic acids (HAs) show photothermal activity and can be used as a photosensitizer for photothermal therapy. In the presence of various functional groups, HAs are endowed with anti-inflammatory and antioxidant activities. The solubility of HAs is dependent on the pH value, which is soluble in neutral to alkaline conditions and undergoes a conformational change to a coiled and compact structure in acidic conditions. Additionally, Cu2+ is an emerging therapeutic agent for cutaneous wounds and can be chelated by HAs to form complexes. In this study, we explore the ability of HAs to modulate the inflammatory response, particularly macrophage polarization, and the potential underlying mechanism. We fabricate a near-infrared (NIR)/pH dual-responsive Cu-HAs nanoparticle (NP)-based poly(vinyl alcohol) (PVA) hydrogel film loaded with SEW2871 (SEW), a macrophage recruitment agent, to treat bacteria-infected cutaneous wounds. The results show that HAs could promote M2 macrophage polarization in a dose-dependent manner. The Cu-HAs NPs successfully eradicated bacterial infection through NIR-induced local hyperthermia. This PVA@Cu-HAs NPs@SEW hydrogel film improves tissue regeneration by promoting M2 macrophage polarization, alleviating oxidative stress, enhancing angiogenesis, and facilitating collagen deposition. These findings highlight the therapeutic potential of PVA@Cu-HAs NPs@SEW hydrogel film for the treatment of bacterially infected cutaneous wound healing.